7
$\begingroup$

So, in order to obtain the required answer, I tried to apply some Taylor expansions, which led me to nowhere actually. After a while I tried to use the summation theorem

$\sum_{n=-\infty}^{+\infty}{f\left(n\right)}=-\sum_{i=1}^{m}{Res_{z=z_i}{\pi\cot\left(\pi z\right)f\left(z\right)}}$ at $f\left(z\right)$'s poles.

Residue at $z=-\frac{1}{2}$ equals to residue at $z=\frac{1}{2}$, both of them are $-\frac{\pi ^2}{16}$. What I got seems to be not the correct answer after all:

$-\sum_{i=1}^{m}{Res_{z=z_i}{\pi\cot\left(\pi z\right)f\left(z\right)}} = -\frac{\pi ^2}{8}$, so that $\sum_{n=-\infty}^{+\infty}{f\left(n\right)}=\frac{\pi ^2}{8}$ Since the $f\left(z\right)$ is even, I get $\sum_{n=0}^{+\infty}{f\left(n\right)}=\frac{\pi ^2}{16}$

However, the initial task was to find the sum of $\sum_{n=1}^{+\infty}{f\left(n\right)}$. I supposed that $\sum_{n=1}^{+\infty}{f\left(n\right)}=\sum_{n=0}^{+\infty}{f\left(n\right)}-f\left(0\right)=\frac{\pi ^2}{16}-1$, which is incorrect, as according to Mathematica, I should get $\frac{\pi ^2}{16}-\frac{1}{2}$. I don't know where is my mistake at this point. Perhaps, the whole approach is not well executed.

$\endgroup$
6
$\begingroup$

Since $\frac{1}{4n^2-1}=\frac{1}{2}\left(\frac{1}{(2n-1)}-\frac{1}{(2n+1)}\right)$ by squaring we get $$\sum_{n\geq 1}\frac{1}{(4n^2-1)^2} = \frac{1}{4}\sum_{n\geq 1}\frac{1}{(2n-1)^2}+\frac{1}{4}\sum_{n\geq 1}\frac{1}{(2n+1)^2}-\frac{1}{4}\sum_{n\geq 1}\left(\frac{1}{2n-1}-\frac{1}{2n+1}\right)$$ where the first two series in the RHS depend on $\zeta(2)-\frac{1}{4}\zeta(2)=\frac{\pi^2}{8}$ and the last one is telescopic: $$ \sum_{n\geq 1}\frac{1}{(4n^2-1)^2}=\color{blue}{\frac{\pi^2-8}{16}}.$$

$\endgroup$
4
$\begingroup$

$\newcommand{\bbx}[1]{\,\bbox[15px,border:1px groove navy]{\displaystyle{#1}}\,} \newcommand{\braces}[1]{\left\lbrace\,{#1}\,\right\rbrace} \newcommand{\bracks}[1]{\left\lbrack\,{#1}\,\right\rbrack} \newcommand{\dd}{\mathrm{d}} \newcommand{\ds}[1]{\displaystyle{#1}} \newcommand{\expo}[1]{\,\mathrm{e}^{#1}\,} \newcommand{\ic}{\mathrm{i}} \newcommand{\mc}[1]{\mathcal{#1}} \newcommand{\mrm}[1]{\mathrm{#1}} \newcommand{\pars}[1]{\left(\,{#1}\,\right)} \newcommand{\partiald}[3][]{\frac{\partial^{#1} #2}{\partial #3^{#1}}} \newcommand{\root}[2][]{\,\sqrt[#1]{\,{#2}\,}\,} \newcommand{\totald}[3][]{\frac{\mathrm{d}^{#1} #2}{\mathrm{d} #3^{#1}}} \newcommand{\verts}[1]{\left\vert\,{#1}\,\right\vert}$ \begin{align} \sum_{n = 1}^{\infty}{1 \over \pars{4n^{2} - 1}^{2}} & = \left.{1 \over 16}\,\partiald{}{a}\sum_{n = 1}^{\infty}{1 \over n^{2} - a^{2}} \right\vert_{\ a\ =\ 1/2} = \left.{1 \over 16}\,\partiald{}{a}\sum_{n = 0}^{\infty}\pars{% {1 \over n + 1 - a} - {1 \over n + 1 + a}}{1 \over 2a} \right\vert_{\ a\ =\ 1/2} \\[5mm] & = \left.{1 \over 32}\,\partiald{}{a}\pars{H_{a} - H_{-a} \over a} \right\vert_{\ a\ =\ 1/2}\qquad\qquad\quad\pars{~H_{z}:\ Harmonic\ Number~} \\[5mm] & = \left.{1 \over 32}\,\partiald{}{a}\pars{H_{a - 1} + 1/a - H_{-a} \over a} \right\vert_{\ a\ =\ 1/2}\qquad\pars{~H_{z}\ Recursive\ Property~} \\[5mm] & = \left.{1 \over 32}\,\partiald{}{a}\pars{{1 \over a^{2}} - {H_{-a} - H_{a - 1} \over a}}\right\vert_{\ a\ =\ 1/2} \\[5mm] & = \left.{1 \over 32}\,\partiald{}{a}\pars{{1 \over a^{2}} - {\pi\cot\pars{\pi a} \over a}}\right\vert_{\ a\ =\ 1/2} \qquad\pars{~H_{z}\ Euler\ Reflection\ Formula~} \\[5mm] & = \left.{1 \over 32}\pars{-\,{2 \over a^{3}} + {\pi\cot\pars{\pi a} \over a^{2}} + {\pi^{2}\csc^{2}\pars{\pi a} \over a}}\right\vert_{\ a\ =\ 1/2} = \bbx{\pi^{2} - 8 \over 16} \approx 0.1169 \end{align}

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.